Respuestas
Respuesta dada por:
0
Respuesta:
x^3-2x+2
-2x^3-3x^2+2x-3
Explicación paso a paso:
(x^2+2)+(1-x)=x^2-x^3+2-2x=-x^3-2x+2
(x^2+2-1)*(2x-3)=(x^2+1)*(2x-3)=2x^3-3x^2
+2x-3=
hola675031:
gracias^^
Respuesta dada por:
0
Respuesta:
1.x^2-x+2 2.x^2-2x-1
Explicación paso a paso:
Facillllllllllll
Adjuntos:
![](https://es-static.z-dn.net/files/de7/78de191395fbf7b0e54713680a26d459.jpg)
![](https://es-static.z-dn.net/files/d29/c4e27b48561e398ddc3fb74a3fd708ff.jpg)
Preguntas similares
hace 2 años
hace 2 años
hace 2 años
hace 5 años
hace 7 años